FROM POLICY TO PRACTICE: ANALYSIS OF WASTE MANAGEMENT IMPLEMENTATION IN TAMANSARI TOURISM VILLAGE - Hurul Ainun Zulfa Salsabila; Hary Priyanto; Niko Pahlevi Hentika (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The development of Tamansari Village as a leading tourist village in Banyuwangi Regency has had a positive impact on the community's economy, but has also given rise to environmental problems in the form of increased household and tourist waste generation. Suboptimal waste management has the potential to disrupt the sustainability of tourist villages if not balanced with effective policies and community empowerment. This study aims to analyze the implementation of community empowerment-based waste management policies in Tamansari Village using the pressure, opportunity, and rationalization theories. This study uses a qualitative approach with a descriptive research type. Data were collected through in-depth interviews, field observations, and documentation studies. Informants were selected purposively, including village officials, tourist village managers, waste bank managers, community leaders, and villagers. Data analysis was carried out using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing, and its validity was tested through triangulation of sources and techniques. The results of the study indicate that the policy approach is not only technical, but also touches on structural and behavioral aspects, so that community empowerment-based waste management in Tamansari Village can be effective and sustainable. This study concludes that waste management in Tamansari Village requires an integrated approach that addresses both structural and behavioral aspects of the community.